2005
DOI: 10.1002/art.21215
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical injury of cartilage explants causes specific time‐dependent changes in chondrocyte gene expression

Abstract: Objective. Joint injury in young adults leads to an increased risk of developing osteoarthritis (OA) later in life. This study was undertaken to determine if injurious mechanical compression of cartilage explants results in changes at the level of gene transcription that may lead to subsequent degradation of the cartilage.Methods. Cartilage was explanted from the femoropatellar groove of newborn calves. Levels of messenger RNA encoding matrix molecules, proteases, their natural inhibitors, transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
172
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 45 publications
(65 reference statements)
15
172
3
1
Order By: Relevance
“…In contrast, compression injury caused the loss of cell membrane integrity and the release of intracellular proteins, which may cause changes in gene expression and/or trigger apoptosis in neighboring cells. Release of matrix proteins and protein fragments following compression injury suggests damage to the PCM and ECM, consistent with reported decreases in tissue compression and shear stiffness (2,6,14,21,43). Damage to the matrix may also lead to changes in cell-matrix interactions, which could be responsible for apoptosis, for changes in gene expression, or for the decrease in the ability of the remaining viable cells to up-regulate biosynthesis in response to anabolic loading (2,6,14,21,43).…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, compression injury caused the loss of cell membrane integrity and the release of intracellular proteins, which may cause changes in gene expression and/or trigger apoptosis in neighboring cells. Release of matrix proteins and protein fragments following compression injury suggests damage to the PCM and ECM, consistent with reported decreases in tissue compression and shear stiffness (2,6,14,21,43). Damage to the matrix may also lead to changes in cell-matrix interactions, which could be responsible for apoptosis, for changes in gene expression, or for the decrease in the ability of the remaining viable cells to up-regulate biosynthesis in response to anabolic loading (2,6,14,21,43).…”
Section: Discussionsupporting
confidence: 74%
“…Numerous experimental studies have examined the effect of abnormal mechanical loads, resulting in damaged cartilage, on chondrocyte viability and biosynthetic activity. It has been shown that mechanical injury to cartilage explants results in chondrocyte apoptosis with a loss of glycosaminoglycans [58] and changes in gene expression [59]. Similarly, Borelli Jr. et al [60] have shown that in vivo chondrocyte apoptosis can be caused by a single impact load.…”
Section: Discussionmentioning
confidence: 99%
“…14 Dynamic compression has been shown to upregulate expression of anabolic genes such as ACAN, COL2 α1 (COL2A1), and tissue inhibitor of metalloproteinase 3 (TIMP3) 15 while downregulating specific genes of the matrix metalloproteinase (MMP) family. 4,9,15,16 More importantly, compressive forces at low magnitudes have been shown to be antiinflammatory in nature. This is evidenced by the findings that when chondrocytes seeded into agarose hydrogel scaffolds were stimulated by exogenous interleukin-1β (IL-1β), sinusoidal form compression at 15% strain suppressed aggrecanase 1 (a disintegrin-like and metalloprotease domain (reprolysin-type) with thrombospondin type I motifs 4 [ADAMTS4]) and aggrecanase 2 (ADAMTS5) but not MMP3 gene expression.…”
Section: A Compressive Forces Regulate Cartilage Damage and Repairmentioning
confidence: 99%
“…[21][22][23] Similarly, long-term (24-48 hours) compressive strain of 25% to 50% is catabolic and substantially downregulates expression of ACAN and COL2A1 and upregulates MMP3, MMP9, MMP13, and ADAMTS4 expression to induce cartilage destruction. 16,24 Contrary to dynamic loading, static compression induces an initial accumulation of interstitial hydrostatic pressure within the cartilage; however, this pressure reaches an equilibrium stasis due to stress relaxation of the tissue. 3 Static compression invariably downregulates anabolic gene expression 4,12,16 and upregulates catabolic (MMP3, MMP9, MMP13, and ADAMTS4) 4 and inflammatory (tumor necrosis factor-α [TNF-α; TNFA], COX2/PTGS2, iNOS/NOS2A).…”
Section: A Compressive Forces Regulate Cartilage Damage and Repairmentioning
confidence: 99%
See 1 more Smart Citation